An Overview of Antiemetic Prophylaxis for Chemotherapy Induced Nausea and Vomiting in Head and Neck Cancer Patients at Dharmais National Cancer Hospital - Sari, Novita; Sauriasari, Rani; Putri, Risani Andalasia (Indonesian Journal of Cancer, 2025)
Background: Chemotherapy-induced nausea and vomiting (CINV) are frequently experienced by cancer patients. One of the antineoplastic agents with high emetogenicity is cisplatin. Cisplatin is commonly used in the treatment of head and neck cancer (HNC). Therefore, the use of prophylactic antiemetics is recommended. This study aimed to examine the use of antiemetics as prophylaxis for CINV in HNC patients.Method: This study is a cross-sectional, using retrospective data from medical record observations at Dharmais National Cancer Hospital. Purposive sampling was used to collect data on antiemetic use between October and December of 2023. All patients with HNC who were undergoing chemotherapy and receiving antiemetics as prophylaxis during this period were included in the study and analyzed descriptively.Results: A total of 177 chemotherapy cycles in 96 head and neck cancer patients included in this study indicated that the most commonly used prophylactic antiemetic was a combination of ondansetron and dexamethasone (83.1%). The experience of CINV occurred more frequently in the delayed phase, with nausea occurring in 64.4% and vomiting in 44.6%. The highest severity level of nausea occurred at grade 2 (50.8%), meanwhile vomiting occurred at grade 1 (55.9%).Conclusion: The findings of this study show that the use of 5-HT3 RA (ondansetron) and dexamethasone alone is not sufficient to reduce the CINV response, thus requiring additional therapy such as D-2 RA, PPI, and H-2 Blockers.